2014
DOI: 10.1002/2013ja019527
|View full text |Cite
|
Sign up to set email alerts
|

Cassini nightside observations of the oscillatory motion of Saturn's northern auroral oval

Abstract: In recent years we have benefitted greatly from the first in-orbit multi-wavelength images of Saturn's polar atmosphere from the Cassini spacecraft. Specifically, images obtained from the Cassini UltraViolet Imaging Spectrograph (UVIS) provide an excellent view of the planet's auroral emissions, which in turn give an account of the large-scale magnetosphere-ionosphere coupling and dynamics within the system. However, obtaining near-simultaneous views of the auroral regions with in situ measurements of magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 67 publications
4
15
0
Order By: Relevance
“…The observed particles and waves are consistent with similar observations discussed in Mitchell et al (2009a) that have previously been associated with auroral activity on both open and closed field line configurations (as determined by energetic electron anisotropies). The pulsations seen in the in situ data are similar to those discussed in Mitchell et al (2009a), Badman et al (2012), Jasinski et al (2014), and Bunce et al (2014), although in this event we do not have the required data to make a direct inference regarding the field topology.…”
Section: Discussion/conclusionsupporting
confidence: 56%
See 1 more Smart Citation
“…The observed particles and waves are consistent with similar observations discussed in Mitchell et al (2009a) that have previously been associated with auroral activity on both open and closed field line configurations (as determined by energetic electron anisotropies). The pulsations seen in the in situ data are similar to those discussed in Mitchell et al (2009a), Badman et al (2012), Jasinski et al (2014), and Bunce et al (2014), although in this event we do not have the required data to make a direct inference regarding the field topology.…”
Section: Discussion/conclusionsupporting
confidence: 56%
“…Radioti et al (2013) showed two ''rebrightenings'' of the bifurcations of the main emissions, with an interval of 1 h, but no other mention has been made of the repeated brightening at about a 1 h period in the auroral data. There has been no association made between these repeated auroral events and the 1 h pulsations observed regularly in the radio wave and particle data, for example in Mitchell et al (2009a), Jasinski et al (2014), Bunce et al (2014). Badman et al (2012) showed the correspondence of similar 1 h pulsations in the in situ data with the presence of conjugate auroral arcs, but did not have the temporal resolution to observe any intensity variations in the auroral emissions.…”
Section: Introductionmentioning
confidence: 84%
“…Nevertheless, on the basis of our results we would expect the main upward current layer, sheet 2, to be associated with the main UV oval emissions, and that a secondary narrower dimmer emission associated with sheet 4 should generally be present ~2° equatorward of it. Although the structure of nightside emissions has yet to be the subject of large‐scale study at this level of detail, examples of such multiple nightside arcs are known in the literature [ Melin et al ., ; Bunce et al ., ]. With regard to modulation by the PPO oscillation, we note that the total current and the current density in upward current sheet 2 are modulated by a factor of more than ~2 over the PPO cycle, which should lead to strong variations in the emission intensity in proportion to the square of the current density, while the related modulations in sheet 4 are significantly smaller.…”
Section: Four‐current Sheet Analysismentioning
confidence: 90%
“…These data were discussed both individually and statistically by Talboys et al [, ] and Bunce et al [] and more recently by Hunt et al [, ]. Later in the second high‐latitude interval, extending into 2009, the periapsis distance was again beyond ~10 R s , such that traversals of the auroral field lines were slower and partial [ Bunce et al , ], and thus less suitable for the present study.…”
Section: Introductionmentioning
confidence: 96%